2018
DOI: 10.1111/1744-9987.12668
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Artery Calcification Score Is a Marker of Vascular Calcification in Male Hemodialysis Patients

Abstract: Patients who undergo hemodialysis often suffer from cardiovascular disease (CVD), and evaluation of coronary artery calcification is extremely important. These evaluations are typically conducted using a noninvasive method including electron beam computed tomography (CT) or multi-detector CT, and the Agatston method to calculate the coronary artery calcification score (CACS). However, it is difficult to use for patients undergoing dialysis. Because patients undergoing dialysis is too strong in coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…They found that calcification increases with time on dialysis. 13 A recent study by Marcuzzi et al is comparable with our study. Those authors also used Agatston score to evaluate potential kidney recipients' level of iliac artery calcification.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They found that calcification increases with time on dialysis. 13 A recent study by Marcuzzi et al is comparable with our study. Those authors also used Agatston score to evaluate potential kidney recipients' level of iliac artery calcification.…”
Section: Discussionsupporting
confidence: 92%
“…They looked at calcification in the pelvic arteries in a well‐defined triangle, but did not include the iliac arteries. They found that calcification increases with time on dialysis 13 …”
Section: Discussionmentioning
confidence: 99%
“…One possible solution could be intima media thickness (IMT) measurement of carotid and peripheral arterial vessels, as it enables an easy diagnosis of early‐stage atherosclerosis 8 . Lately, an increasing interest has been noted regarding the use of coronary artery calcium score (CACS) as a reliable predictor of future CV events in patients with declining renal function, especially in those receiving chronic HD 1,8–11 . However, to the best of our knowledge, the specific tool for CV risk assessment has not yet been proposed by any international guideline concerning the dialysis population.…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐slice CT of the pelvic area found arterial calcification (mainly in the penile arteries) of 80% of 53 HD patients with erectile dysfunction; coronary artery calcification was present in 98% of these patients …”
mentioning
confidence: 99%